Pediatric Rotary Files: Evolution to Revolution: Life Sciences-Dentistry - Dr Neeta S Padmawar; Dr Aparna Palekar; Dr Savita Thakkannavar; Dr Shridhar Shetty; Dr Shilpa Pharande; Dr Swati Pustake (International Journal of Life Science and Pharma Research, 2022)
The main goal of pulp therapy in primary dentition is to preserve the primary tooth thus protecting future normal occlusion. Routinely, pulp debridement and canal shaping are done by manual H-files, K-files, Broach, etc. Manual instrumentation may be time- consuming, thus impacting the behaviour of the child negatively. Thus arises the need for alternate instrumentation which will reduce the time required for treatment with better treatment outcomes. In 1988, Walia et al. introduced Nickel-Titanium (Ni-Ti), which revolutionized the discipline of Endodontics. These Ni-Ti files have advantage of shape memory and super elasticity thus improving the canal preparation and resulting in better shaped canals. In 2002, for first time Barr et al reported the use of rotary Ni-Ti files for the therapeutic purpose during Pulpectomy procedure in pediatric patient. He observed better acceptance by pediatric patient and good quality obturation. Till 2016, pulpectomy procedures were accomplished by the combination of hand files and adult rotary files. Adult rotary files are designed according to the morphology for permanent teeth and adult jaw size, thus the use of adult rotary files are in primary teeth may result in lateral perforation due to softer dentine of roots of primary teeth and may cause discomfort to the child thus making child unco-operative. But in 2016, Ganesh et al., pioneered the specialization of Paediatric Endodontics with his invention of specially designed rotary files. Their shape was specially designated for application in tortuous canals of primary teeth. Presently, a variety of pediatric rotary files like Kedo-STM (India), Pro AF Baby GoldTM (India),PrimePedoTM (India), DXL-ProPedoTM (India), NeolixTM (France),Denco® Kids files (China) and, Sani® Kid rotary files (China). This review is an album of these newer files and clinical and in-vitro research on them.